Socio-Economic Dimensions of Unemployment and Strategies for Addressing It: A Descriptive Study - Hafshah Marwa Musthafa (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Unemployment is a multidimensional socio-economic problem that manifests in various forms, each driven by distinct causes and requiring specific solutions. This study addresses the problem of identifying the different types of unemployment and the challenges in determining appropriate strategies to mitigate them. The objective of this research is to analyze the classifications of unemployment, explore their underlying causes, and propose suitable approaches for their treatment based on both classical economic theory and complementary perspectives. This research employs a descriptive qualitative method, relying on literature review and analytical interpretation of traditional economic theories alongside expanded categorizations observed by the researcher. The study examines the linguistic and terminological definitions of unemployment, its various types, and practical strategies for addressing it. The findings reveal that understanding the specific type of unemployment is essential for diagnosing its root causes and implementing effective solutions. Traditional classifications alone are insufficient; therefore, integrating complementary categories provides a more comprehensive framework for analysis and intervention. This study contributes to the enrichment of socio-economic discourse by offering a nuanced classification of unemployment and highlighting the importance of context-specific solutions. It also bridges insights from economic theory with broader intellectual perspectives, supporting more effective policy formulation and academic inquiry.